Thiophene‐fused‐heteroaromatic diones as promising NIR reflectors for radiative cooling - Chen, Wangqiao (2020)
Developing appropriate NIR‐reflective materials to combat near–infrared (NIR) heat radiation (700–2500 nm) from sunlight, avoiding energy accumulation and reduce energy consumption, is important and highly desirable. In this research, four thiophene‐fused‐heteroaromatic diones were used as basic reflectors to investigate the relationship between their intrinsic molecular structures and NIR‐reflective properties. The reflectance intensity can be readily tuned by adjusting the length of the appended aliphatic side chains, as well as the strength of the electron‐donating groups. A methoxy‐substituted thiophene‐fused‐heteroaromatic dione showed the best performance in reflecting NIR, and it was used as a coating for a model glass house. The comparison of the internal temperature difference relative to a control house was measured and the maximum temperature was 12 °C lower than that in the control house.